Feature extraction on forearm using surface electromyography (sEMG) technique - Khoo, Hui Ping; Chong, Shin Horng; Yahya , Abu Bakar (2014)
This study discussed about the measurement of muscle fatigue analysis using surface electromyography (sEMG). The analysis for feature extraction involved in this paper is time domain, frequency domain and time-frequency domain. The result based on amplitude of signal and frequency in either frequency domain or time-frequency domain shifting will be covered.